Generic eVTOL aircraft preliminary sizing method for AAM/UAM missions - Kahn, Y.M.; Balli, M.E.; Trainelli, L. (My University, 2022)
Advanced Air Mobility (AAM) or Urban Air Mobility (UAM) presents many challenges to the aircraft design. The concept not only requires operations over urban airspace but also without the use of traditional airports with long runways. Additionally, the new aircraft designs must do so on electric power as much as possible with low chemical and noise emissions. Hence the term electric vertical takeoff and landing or eVTOL is popularized. This paper presents a novel method for preliminary sizing of eVTOL aircraft of arbitrary architecture. The methodology allows the conceptual analysis and initial trade-off studies independent of the aircraft configuration. Aircraft is considered as the sum of building blocks like rotors, propellers, wings, and several other subsystems contributing to mass, energy, power and drag estimates. Results from this study permit a quick evaluation of configurations and missions with an inevitable degree of approximation. Finally, the main features of the method are discussed in the paper with a relevant validation exercise for various eVTOL aircraft considering mass and other performance metrics.